Selective Serotonin Reuptake Inhibitors in Human Pregnancy: To Treat or Not to Treat? - Orna Diav-Citrin; Asher Ornoy (Obstetrics and Gynecology International)
Selective serotonin reuptake inhibitors (SSRIs) are increasingly prescribed during pregnancy. The purpose of the present paper is to summarize and evaluate the current evidence for the risk/benefit analysis of SSRI use in human pregnancy. The literature has been inconsistent. Although most studies have not shown an increase in the overall risk of major malformations, several studies have suggested that SSRIs may be associated with a small increased risk for cardiovascular malformations. Others have noted associations between SSRIs and specific types of rare major malformations. In some studies, there appears to be a small increased risk for miscarriages, which may be associated with the underlying maternal condition. Neonatal effects have been described in up to 30% of neonates exposed to SSRIs late in pregnancy. Persistent pulmonary hypertension of the newborn has also been described with an absolute risk of <1%. The risk associated with treatment discontinuation, for example, higher frequency of relapse and increased risk of preterm delivery, should also be considered. The overall benefit of treatment seems to outweigh the potential risks.